Convergence between absorptive capacity and knowledge appropriation: A new methodology Mapping the hidden links - Sergio Cuéllar; María Teresa Fernández-Bajón; Félix De Moya-Anegón (Journal of Open Innovation: Technology, Market and Complexity, 2024)
This study investigates the relationship between Absorptive Capacity (AC) and Knowledge Appropriation (KA), two significant domains in technology transfer, knowledge management, and innovation. While there is an inherent connection between these fields, there remains a gap in understanding their comprehensive convergence. To address this, we reviewed 3412 AC and 368 KA articles, employing techniques such as life-cycle, changepoint, and advanced keyword analyses. We also introduced innovative methods like the H-index, CAGR, and a unique approach comparing keyword frequency over time between AC and KA, spotlighting key convergence areas: innovation, entrepreneurship, and knowledge spillover.Our analysis revealed a parallel evolution of AC and KA, as demonstrated by their shared timelines, thematic overlaps, and mutual influences in the realm of innovation. The life-cycle analysis showed a faster evolutionary pace for AC than for KA but highlighted their shared roots in management during the late 80s. Furthermore, we identified foundational building blocks, including patents, R&D, and knowledge management, that underpin their convergence. Interestingly, some divergent areas were also pinpointed, such as the emphasis on organizational learning in AC but its absence in KA.In summary, this study provides a clear picture of the intertwined relationship between AC and KA, presenting a refined methodology to explore convergence between academic fields, setting the stage for further research in this domain.